Logarithmic derivatives of diffusion measures in a Hilbert space - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For the logarithmic derivative of transition probability of a diffusion process in a Hilbert space, we construct a sequence of vector fields on Riemannian n-dimensional manifolds that converge to this derivative.